Revolusi Mental Dalam Pandangan Akhlak - Susanti, Reni; Deswita, Deswita (BELAJEA: Jurnal Pendidikan Islam, 2016)
This paper aims to make a change of a personâs things from bad manner to better one. So the writer takessome referencesabout the opinion of IbnMiskawayh and al-Ghazhali.This mental revolution examines mental problems in view of morals. The target of the work of moral itself is a mental character or characters. Mental revolution is a change of characters that originated from a persons way of dayly life.The scope of howto change the characters and the character of a person is the habit of a persons life, which ultimately extends to lifestyle of nation or state. Mental revolution can not be separated from moral education and mental, therefore, the purpose of education in Islam is a moral education or coaching mental learners for better mental and spirited professional.It is expected from Islamic education for a human soul in full awareness of itself, in terms of an increase of hablumminannas and hablumminallah point. So that, it would appear that the concept of the perfect man became agoal of Islamic Education. Because the goal of Islamic education is to make the perfect man outwardly and spiritually.